2011
DOI: 10.1038/onc.2011.31
|View full text |Cite|
|
Sign up to set email alerts
|

OTX1 expression in breast cancer is regulated by p53

Abstract: The p53 transcription factor has a critical role in cell stress response and in tumor suppression. Wild-type p53 protein is a growth modulator and its inactivation is a critical event in malignant transformation. It has been recently demonstrated that wild-type p53 has developmental and differentiation functions. Indeed an overexpression of p53 in tumor cells induces asymmetrical division avoiding self-renewal of cancer stem cells (CSCs) and instead promoting their differentiation. In this study, 28 human brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…OTX1 has been described as a critical molecule for neocortex organization and determines progenitor behavior and histogenesis in mammals . In addition, it has been reported that the P53 protein directly induces OTX1 expression by acting on its promoter in breast cancer, and synergistically effected cancer stem cell differentiation . Our data showed the OTX1 mRNA was upregulated in gastric cancer, which has not previously been reported.…”
Section: Discussionsupporting
confidence: 48%
“…OTX1 has been described as a critical molecule for neocortex organization and determines progenitor behavior and histogenesis in mammals . In addition, it has been reported that the P53 protein directly induces OTX1 expression by acting on its promoter in breast cancer, and synergistically effected cancer stem cell differentiation . Our data showed the OTX1 mRNA was upregulated in gastric cancer, which has not previously been reported.…”
Section: Discussionsupporting
confidence: 48%
“…In the control samples, we found basal expression of all genes. In PVR samples, we found little (samples 1, 2, 3, 4, 8, 9, and 10) or no expression (samples 5, 6, 7, 11, and 12) of Otx1, attesting the nondifferentiated state of retinal tissues [23], and variable expressions of VEGF-A, Otx2, Otx3, p53, and p63. We found high Otx3 levels in samples with little levels of Otx2 (samples 3 and 4) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Using gene manipulation, we revealed for the first time the involvement of p53 and Cav-1 in CSC acquisition and cell aggressiveness induced by SWCNTs (Figure 7C, 8A and B). It has been recently demonstrated that wild-type p53 positively regulated cell differentiation in breast cancer cells and loss of p53 favored CSC growth [40,41]. However, the functional role of Cav-1 in CSC induction is not known.…”
Section: Discussionmentioning
confidence: 99%